2011
DOI: 10.1007/s10856-011-4420-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chitin-PAA-GTMAC gel in promoting wound healing: animal study

Abstract: Acrylic grafted chitin (chitin-PAA) was modified with glycidyltrimethylammonium chloride (GTMAC) with the aim of promoting wound healing. The chitin-PAA-GTMAC gels with different GTMAC contents were compared with the original chitin-PAA gel and Intrasite gel for their efficacy in deep wound healing of Wistar rats. Four full-thickness wounds were made on the dorsal skin of rats and then each was treated with 4 materials; chitin-PAA, chitin-PAA-GTMAC(1:4), chitin-PAA-GTMAC(1:10) and Intrasite gel. During 18 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…This makes them promising for incorporation into wound healing and implantable biomaterials. Pilakasiri et al found that QA-modified chitin gels are promising candidates for treatment of full-thickness open wounds, with better wound healing than a clinically available dressing [223].…”
Section: Sutures and Wound Dressingsmentioning
confidence: 99%
“…This makes them promising for incorporation into wound healing and implantable biomaterials. Pilakasiri et al found that QA-modified chitin gels are promising candidates for treatment of full-thickness open wounds, with better wound healing than a clinically available dressing [223].…”
Section: Sutures and Wound Dressingsmentioning
confidence: 99%
“…The type of polymerization to be selected depends on the type of monomer to be grafted; in most cases, radical polymerization has been used [82,83,84,85,86,87,88,89], although there is also a report of anionic ring-opening polymerization [90]. Acrylic monomers (especially acrylic acid) are among the most frequently grafted into chitin [82,83,84,85,88,91,92,93]. For the development of experimental procedures, it must be taken into account that chitin is not soluble in aqueous media and, therefore, the reaction must be carried out mostly under heterogeneous conditions.…”
Section: Graft Copolymerizationmentioning
confidence: 99%
“…The other free radical initiator that has been successfully used for the grafting of acrylic monomers onto chitin is potassium persulfate [85,88,91,92]. Hydrogels prepared with chitin- g -poly(acrylic acid) by the grafting from method have been proposed as a wound dressing material [85,91,92]. The highly water-absorbable film showed a good capacity of absorbing exudates from wounds, thus keeping a moist wound environment [85].…”
Section: Graft Copolymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we report simple and efficient alternatives for the modification of chitosan: dendronization with a biocompatible dendron; 13 a quaternization process with an ammonium salt, such as glycidyl trimethylammonium chloride (GTMAC), which confers a permanent positive charge to the polymer; and a combination of both methodologies to form a amphiphilic polymer.…”
Section: ■ Introductionmentioning
confidence: 99%